Derivatization‐free method for compound‐specific isotope analysis of nonexchangeable hydrogen of 4‐bromophenol. (12th March 2019) - Kuder, Tomasz; Bernstein, Anat; Gelman, Faina
Abstract : Rationale: Compound‐specific isotope analysis (CSIA) is a valuable tool in environmental chemistry and in other fields of science. Currently, hydrogen CSIA of polar compounds containing exchangeable hydrogen is uncommon. To extend the scope of CSIA applications, we present an alternative method of analysis, bypassing the typical step of derivatization. The method is demonstrated for two environmental contaminants, 4‐bromophenol (4BP ) and 2, 4, 6‐tribromophenol (TBP). Methods: Net isotope ratios obtained by CSIA combine the isotope composition of nonexchangeable, carbon‐bound hydrogen and the exchangeable hydroxyl hydrogen. To constrain the isotope composition of the latter, an ethyl acetate solution of 4BP or TBP injected into the IRMS instrument was amended with excess water of known isotope composition. The results were calibrated using bracketing control samples analyzed in sequence with the unknown samples and the known isotope ratios of water present in ethyl acetate solution. Results: The analytical precision was comparable to the precision for halogenated compounds without exchangeable hydrogen, analyzed using similar instrumentation. The isotope ratios of the bromophenols correlated with the isotope composition of the water in the sample matrix, suggesting that the hydroxyl group of the target compound remained close to the equilibrium with the sample water during the passage through the instrument. Based on this relationship, the signatures of the nonexchangeable hydrogen were obtained using the isotope composition of sample water as the proxy for the isotope composition of the target compound hydroxyl group. Conclusions: The developed method could be adopted to analysis of other low molecular weight compounds amenable to gas chromatography without the absolute need for derivatization. Currently, the method can be used for samples from laboratory experiments, with high concentrations of the target compound to provide mechanistic insight into the degradation mechanisms. Further work would be required to optimize the method to low concentration environmental samples.